The Impact of Work Stress on Job Satisfaction and Sleep Quality for Couriers in China: The Role of Psychological Capital - Xie, Yujin; Tian, Jing; Jiao, Yang; Liu, Ying; Yu, Hong; Shi, Lei (Frontiers in Psychology, 2021)
Objective: Work stress is one of the urgent public health problems, which has aroused wide attention. In addition, work stress also has a negative impact on the development of enterprises. This study has three purposes :(1) to understand the current status of working stress among couriers; (2) to examine the association between work stress, job satisfaction and sleep quality of Chinese couriers, and (3) to verify the mediating role of psychological capital. Methods: A cross-sectional survey was conducted among 3000 couriers in Beijing of China from January to December 2019 using cluster stratified random sampling. Descriptive statistical analysis was used to describe demographic characteristics of respondents. Pearson correlation analysis was used to analyze the correlation among work stress, job satisfaction, sleep quality and psychological capital. The mediating analysis was calculated role of psychological capital. Results: A total of 2831 participants were included in this study. The average score of work stress was 2.49±0.76. Work stress was negatively correlated with job satisfaction (r=−0.266, P<0.01), sleep quality (r=−0.142, P<0.01) and psychological capital (r=−0.266, P<0.01), respectively. The direct effect of work stress on job satisfaction is -0.223, and the total effect of work stress on job satisfaction is -0.267. The a*b*c′ is positive, indicating the mediating role psychological capital has in explaining the relationship between couriers’ work stress and job satisfaction. Moreover, psychological capital plays a mediating role between work stress and sleep quality among couriers. Conclusions: Couriers face certain work stress and should be paid attention to and psychological capital can effectively alleviate the work stress of couriers, so measures can be taken to improve it, promoting healthy development of employees and organizations.